Aplikasi Model Teams Games Tournament Berbasis Kartu Domino Matematika (DOMAT) untuk Meningkatkan Keterampilan Hitung - Putri, Prihastini Oktasari; Khotimah, Khusnul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study originated from the low numeracy skills of students, in which only 5 out of 33 students were able to solve the problems correctly. The purpose of this study was to improve students’ numeracy skills through the implementation of the Teams Games Tournament (TGT) model using Mathematics Domino Cards (DoMat) as learning media in Grade III of SD Negeri Salit. The research subjects consisted of 33 students, including 15 female students and 18 male students. This study employed Classroom Action Research. Data were collected through formative tests to measure students’ numeracy skills and non-test techniques in the form of observation sheets to examine learning activities. Data analysis techniques included quantitative descriptive analysis for test results and qualitative descriptive analysis for observation data. The results showed an increase in the percentage of students’ mastery of numeracy skills from 33.33% in the pre-cycle to 66.66% in Cycle I, and further increased to 87.87% in Cycle II. These findings indicate that the TGT model with DoMat cards is effective in improving students’ numeracy skills.